Operative Learning Model Using The 'Snowball Throwing' Method in Teaching Mandarin Vocabulary - Pambudi, Pratama Priya; Siregar, Sheyra Silvia; Marsuki, Ria Riski (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to investigate the effectiveness of the Snowball Throwing learning model in improving students’ reading skills in Mandarin language classes. The research was conducted at SMA PL Don Bosko Semarang with students of class XII 5 as participants. A quantitative approach was employed using a one-group pretest-posttest design. Data were collected through reading tests administered before and after the application of the learning model. The results showed a significant increase in students’ posttest scores, indicating that the Snowball Throwing model had a positive impact on students' Mandarin reading abilities. The interactive and collaborative nature of the model encouraged active student participation and enhanced comprehension through peer discussion. These findings suggest that Snowball Throwing is an effective strategy for improving reading skills in foreign language learning, particularly in high school settings. reading skills.